Blockchain for real world applications - Garg, Rishabh (John Wiley & Sons, Inc., 2023)
"Distributed Ledger Technology (DLT) is a technical infrastructure and protocol that allows simultaneous access, verification and updating of records in an irreversible manner over a network spanning multiple entities or locations. It can be a Blockchain, Directed Acylic Graph, Hashgraph, Holochain or Tempo (radix). The blockchain ecosystem includes blocks - the data structure used to keep records of transactions, which are distributed among all nodes in the network, and nodes - users or computers that hold a complete copy of the record or ledger. Blockchain uses an asymmetric cryptography mechanism to validate the authenticity of transactions. The hash function used here is a mathematical algorithm that converts any information into a string of alphanumeric values by a process called encryption. There are mainly two types of encryption - asymmetric encryption and symmetric encryption depending on whether same or different keys are used for encryption and decryption. Decentralized identifiers (DID) allow unique, private and secure peer-to-peer connections between two parties on a blockchain. DIDs are independent of centralized registries, authorities or identity providers, which enable identity-owner control and sovereignty over identities. There have been several innovations around blockchain consensus mechanisms, constitutional design, development of smart contracts, and tokens. Earlier, applications were mainly restricted to digital currencies, which were used in commercial transactions. The extension of Blockchain 2.0 applications enabled smart-contracts, Decentralized Applications (dApps), and Decentralized Autonomous Organizations (DAOs). Blockchain 3.0 was able to register its presence in areas such as education, health, science, transportation and logistics, and now Blockchain 4.0 is evolving as a business-friendly ecosystem for the world of commons."--